Women escaping domestic violence to achieve safe housing: an integrative review - Virginia Stulz; Lyn Francis; Anshu Naidu; Rebecca O'Reilly (BMC, 2024)
Abstract Background This integrative review summarises original research that explores women's experiences of escaping domestic violence to achieve safe housing. Methods Integrative review. A robust search strategy was conducted using the following databases: Scopus, Cumulative Index to Nursing and Allied Health (CINAHL), Cochrane, Medline and PubMed. All articles were assessed for quality using the Mixed Methods Appraisal Tools (MMAT) scoring. Whittemore and Knafl's (2005) five stage approach was used to analyse the primary literature related to women's and stakeholders' experiences of escaping domestic violence to achieve safe housing. Results A total of 41 articles were retrieved and 12 papers were included in this review (six qualitative, one quantitative and five mixed methods) that fulfilled the inclusion criteria. Four overarching themes were identified: 'Experiences of leaving domestic violence', 'Barriers to achieving safe housing', 'Facilitators to achieving safe housing' and 'The road to recovery'. The 'Experiences of leaving domestic violence' theme included two subthemes: 'the losses' and 'ongoing contact with the perpetrator'. The 'Barriers to achieving safe housing' theme included three subthemes: 'financial insecurity', 'being judged by others for leaving and service availability'. The 'Facilitators to achieving safe housing' theme included two sub-themes: 'support, partnership, and collaboration between women and service providers' and 'feeling respected and heard'. The 'Road to recovery' theme included two sub-themes: 'being a good mother' and 'empowerment after leaving domestic violence'. Conclusions This review has highlighted the need for service and health care providers to work together and collaborate effectively with the woman experiencing and escaping domestic violence, especially in rural and remote areas. This means giving women access to the most suitable educational resources and services that are appropriate for their unique situation. Tailoring support for women is crucial to enable women to achieve safe housing and to be able to live a safe life with their children, away from the perpetrator of the domestic violence.